Pola Asuh Daikichi Dalam Film Usagi Drop - Komang Ayu Pradnya Paramitha; Putu Dewi Merlyna Yuda Pramesti; Gede Satya Hermawan (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to identify and find out the parenting style of the character Daikichi in the film Usagi Drop. This research is a qualitative descriptive study. The subject of this research is the character Daikichi in the film Usagi Drop. The analysis techniques used in this research are data collection, data reduction, data display, and conclusion. This research use data collection as the method to observe and analyze Daikichi by notes and data cards. The result of this research is parenting style that can be grouped into 1) Taking part in children's activities, 2) Instilling disciplinary values, 3) Prioritizing time together.